2008
DOI: 10.1016/j.socec.2007.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Economic and hypothetical dictator game experiments: Incentive effects at the individual level

Abstract: The paper compares behavior in economic dictator game experiments played with actual money (amounts given by "dictator" subjects) with behavior in hypothetical dictator game experiments where subjects indicate what they would give, although no money is actually exchanged. The average amounts transferred in the two experiments are remarkably similar. Moreover, we uncover meaningful individual differences in real and hypothetical allocations and demonstrate the importance of two personality traits-agreeableness … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
74
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(79 citation statements)
references
References 27 publications
3
74
1
1
Order By: Relevance
“…Pooling generous and strongly generous subjects results in a fraction of 62% in the incentivized and 48% in the hypothetical treatment; yet this difference is not significant (Fisher's exact test, p = 0.10, two-sided). This pattern is in line with Ben-Ner et al (2008), who also found insignificantly greater generosity for real rather than hypothetical choices in DGs.…”
Section: Figure 1: Results Of the Behavioral Subcategories (By Treatmsupporting
confidence: 87%
See 1 more Smart Citation
“…Pooling generous and strongly generous subjects results in a fraction of 62% in the incentivized and 48% in the hypothetical treatment; yet this difference is not significant (Fisher's exact test, p = 0.10, two-sided). This pattern is in line with Ben-Ner et al (2008), who also found insignificantly greater generosity for real rather than hypothetical choices in DGs.…”
Section: Figure 1: Results Of the Behavioral Subcategories (By Treatmsupporting
confidence: 87%
“…Amir et al (2012) reported that 1$ incentives in an online DG significantly decreased average offers compared to a no-stakes DG. On the contrary, Ben-Ner et al (2008) showed that dictators facing decisions involving real money were slightly more generous compared with participants considering hypothetical money, but this difference was not significant in statistical and economic terms, even after controlling for subject-specific characteristics. Table 1 displays how the pooled decisions map into different categories of social preferences.…”
Section: Introductionmentioning
confidence: 72%
“…In educational studies, a number of works demonstrate the importance of student attitudes or latent family characteristics (OECD 2009;Jakubowski and Pokropek 2009). Behavioral economics often looks into the ways personality traits or attitudes affect people's behavior, for example, in experiments analyzing risk aversion or economic preferences (see Fairlie and Holleran 2012;Grabner et al 2009;Ovchinnikova et al 2009;Ben-Ner et al 2008).…”
Section: Modeling Latent Variablesmentioning
confidence: 99%
“…Recent research has indicated, however, that the presence or absence of an incentive is unrelated to the outcomes observed in dictator games (Ben-Nera et al 2008, Engel 2010.…”
Section: Respondent Characteristicsmentioning
confidence: 99%